2018
DOI: 10.1097/md.0000000000011219
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and antimicrobial susceptibility of human Clostridium difficile isolates from a single institution in Northern China

Abstract: Because the epidemiology of Clostridium difficile infection (CDI) is region-specific, the present study was undertaken to examine the epidemiology of C difficile outbreaks in Beijing, China.Eighty nonduplicate isolates were collected from March, 2016 to December, 2016. The molecular type and phylogenetic analysis were evaluated by multilocus sequence typing (MLST). The minimum inhibitory concentrations (MICs) for 11 antibiotics and the resistance mechanisms were investigated.Sixty-five toxigenic strains (81.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 51 publications
4
6
0
Order By: Relevance
“…We detected only a C656T nucleotide substitution within the 23S rRNA copy on the genome with CARD. However, as a previous study suggested, the substitution has been not associated with conferring resistance to macrolides and lincosamides in C. difficile [41]. Our findings obtained from the resistome analysis seem to be sound and coincide with phenotypic results of antibiotic MICs.…”
Section: Resultssupporting
confidence: 82%
“…We detected only a C656T nucleotide substitution within the 23S rRNA copy on the genome with CARD. However, as a previous study suggested, the substitution has been not associated with conferring resistance to macrolides and lincosamides in C. difficile [41]. Our findings obtained from the resistome analysis seem to be sound and coincide with phenotypic results of antibiotic MICs.…”
Section: Resultssupporting
confidence: 82%
“…difficile , these studies have been based on ribotyping and had a purely descriptive approach 26 . The comparison of the findings with studies worldwide reveals a similar profile in that ST-8, the most frequent in this study, has been reported in the United Kingdom 27 , Australia 28 , China 29 and United States 30 , usually associated with recurrent infections, in coinfection with a second ST, also showing substitutions associated with resistance to antibiotics (at the level of gyrA and gyrB ) 27,29 .…”
Section: Discussionsupporting
confidence: 84%
“…RT 018 is now the most common C. difficile strain reported from Korea, where it has largely replaced RT 017 [23,74]. RT 012/ST54 and RT 046/ST35 localise to China in particular [75,76,77,78,79], RT 014/020/ST2/14 is widespread across the continent [31], and RT 002/ST8 is most frequently reported from Taiwan and Hong Kong [31,80].…”
Section: Epidemiology Of CDI In Asiamentioning
confidence: 99%